Perspectives of health care professionals on artificial insemination of donor semen: appraising their knowledge and perceptions: a single institution study in Nigeria - Abiola, Olajide O.; Ajao, Akinlabi E.; Ogunlaja, Olumuyiwa A.; Adeoye, Sunday O.; Ojo, Ayodeji A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Artificial inseminations of donor semen (AID) involve use of heterologous donated semen for conception in infertile couple when indicated or in a single woman desirous of pregnancy. Its practice often requires regulation to address possible ethical and legal issues which may arise. In formulating acceptable guidelines/policies, the perspectives of health professionals and the participants should be considered. Therefore, we sought to explore the knowledge and perception of semen donation for artificial insemination among health professionals. Methods: A cross sectional study conducted on consenting health workers in a single health institution using a structured questionnaire to assess their knowledge and perception on artificial insemination of donor semen (AID). Descriptive and analytical statistics were applied to the data collected with a statistically significant value of <0.05. Results: One hundred and twenty-one health professionals completed the questionnaires. The mean age of the respondents was 27.58±5.5years. Sixty of the respondents were males while 61 were females. Eighty-four of the respondents (69.4%) demonstrated good knowledge of AID while 37 (30.6%) had poor knowledge. Cadre of health professionals and marital status influenced the knowledge of respondents. Perceptions on AID varied among the respondents mostly influenced by psycho-social factors and possible legal disputes on third party reproductive process. None of the male respondents has ever donated semen and willingness to donate semen was low; with anonymity preferred by the willing donors. Conclusions: Substantial knowledge gap of AIDS existed among health professionals which were influenced by cadre and marital status. Psycho-social factors and possible legal disputes influenced their perceptions of AID.